PCR-SSCCP analysis in detecting point mutations targeting rpoB, katG and inhA genes for determining multi-drug resistance in Mycobacterium bovis and Mycobacterium tuberculosis strains - KIDANGAN, ALEX; VERMA, RISHENDRA (The Indian Journal of Animal Sciences, 2014)
The usefulness of polymerase chain reaction-single stranded confirmation polymorphism (PCR-SSCP) for determination of rifampicin and isoniazid resistance in Mycobacterium tuberculosis and M. bovis cultures from human and animal origin was investigated. Mycobacteria (81) in the study included, viz. 12 MDR-TB samples, 35 sputum samples, 3 lung and lymphnode tissues from bovines and 11 M. tuberculosis and 18 M. bovis culture, M. tuberculosis H37Rv and M. bovis BCG strain). All the mycobacterial cultures were characterized on growth characteristics, biochemical test pattern, MTB complex specific IS6110 PCR and species specific 12.7 kb multiplex PCR. PCR-SSCP was used to determine resistance against rifiampin by targeting rpoB gene (305 bp) and isoniazid by targeting katG (237 bp) and inhA (261 bp). Rifampicin resistance was detected by PCR-SSCP in 1 out of 12 MDR-TB samples (8.3%), while isoniazid resistance was detected in 66.7% of MDR-TB samples using PCRSSCP of katG and 75% of MDR-TB samples using inhA SSCP analysis.